Implementation of mutual character education in Elementary School Teachers: An analysis of the application of P5 in schools - Saputri, Novi Eka; Faturrachman, Saddam; Simarmata, Sari W (Universitas Riau Kepulauan, 2025)
Character education is the foundation for shaping the attitudes and behaviors of Indonesia's future generations, based on national values and exemplary conduct This study aims to analyze the implementation of mutual cooperation character among elementary school (SD) teachers through the implementation of the Proyek Penguatan Profil Pelajar Pancasila (P5). The methodology applied in this study uses a quantitative approach with a survey design, where the entire population of teachers at SD AL Amanah Tangerang Selatan is used as a saturated sample. Data were collected using a questionnaire designed based on a Likert scale to measure the understanding and application of mutual cooperation values in the learning process. Data analysis was carried out using descriptive and inferential statistical techniques to identify patterns related to the application of mutual cooperation characters among teachers. The results showed that most teachers were aware of the importance of mutual cooperation characters and tried to integrate them into teaching and learning activities. However, there were differences in the level of application of these values, which were influenced by factors such as school management support and available training opportunities. This study also revealed that the application of mutual cooperation characters not only had a positive impact on the formation of student character, but also strengthened cooperation among teachers. These findings are expected to provide valuable insights for the development of character education programs in schools, as well as encourage increased collaboration in implementing mutual cooperation values in the educational environment.